The emotional rollercoaster of language teaching - Gkonou, Christina; Dewaele, Jean-Marc 1962-; King, Jim 1974- (Psychology of language learning and teaching, 2020)
This book focuses on the emotional complexity of language teaching and how the diverse emotions that teachers experience while teaching are shaped and function. The book is based on the premise that teaching is not just about the transmission of academic knowledge but also about inspiring students, building rapport with them, creating relationships based on empathy and trust, being patient and most importantly controlling one’s own emotions and being able to influence students’ emotions in a positive way. The book covers a range of emotion-related topics on both positive and negative emotions which are relevant to language teaching including emotional labour, burnout, emotion regulation, resilience, emotional intelligence and wellbeing among others. These topics are studied within a wide range of contexts such as teacher education programmes, tertiary education, CLIL and action research settings, and primary and secondary schools across different countries. The book will appeal to any student, researcher, teacher or policymaker who is interested in research on the psychological aspects of foreign language teaching